Strategi Bimbingan Klasikal Dengan Teknik Permainan Simulasi Dalam Meningkatkan Regulasi Diri Peserta Didik Kelas Xi-1 Di Sma Negeri 7 Kediri - Latiefan Nisaa; Intan Prastihastari Wijaya; Ayu Febri Eka Putri (CV. ITTC INDONESIA, 2025)
This study aims to improve students' self-regulation skills through classical guidance services using simulation game techniques. The method employed is Classroom Action Research (CAR) conducted in three cycles with students from class XI-1. The results showed a gradual improvement in self-regulation skills, as indicated by an increase in observation scores from 41.6% in the pre-cycle, which decreased to 38.7% in cycle I, then significantly increased to 56.8% in cycle II, and reached 68.2% in cycle III. The decline in cycle I was caused by students' low ability to manage emotions, lack of self-confidence, and difficulty accepting others' successes. Through modifications in service strategies and reinforcement in cycles II and III, students showed positive development in self-control, personal initiative, and satisfaction with individual and group work outcomes. Factors supporting this improvement include a conducive learning environment, enjoyable game strategies, and a reflective approach that encourages self-awareness. Therefore, simulation game techniques prove to be an effective approach in classical guidance services to develop students' self-regulation skills in a gradual and sustainable manner.